The Effect of Work Training and Work Motivation on Employee Performance in PT. Pln Area Lenteng Agung Jakarta Selatan - Juwita Ramadani Fitria (Kusuma Negara Business School, 2021)
This study aims to test empirically whether the effect of training and motivation is applied to realize employee performance at PT PLN Lenteng Agung Area. Located on Jalan Raya Duren Tiga No.100, South Jakarta, which consists of 50 respondents (37 male and 13 female) using the Slovin sample method. This research uses quantitative descriptive method with data collection techniques, namely by observation and distributing questionnaires / questionnaires. The data analysis techniques used were validity and reliability tests, classic assumption tests (normality, heteroscedasticity, and multicollinearity tests) along with multiple linear regression analysis and simple linear regression analysis which were processed using SPSS 22. The results of this study can be seen from the multiple linear regression equation Y = 9.891+ 0.658X1 + 0.786X2 This can be interpreted that employee performance without the support of training and work motivation (constant) is 9.891 and any changes in the joint increase between the training and work motivation variables will determine the level of employee performance, every one point increase in the training variable due to an increase in the employee performance score of 0.658 and every time there is an increase in job training variables due to an increase in the employee performance score of 0.786. Thus the better the training and work motivation, the higher the level of employee performance. Based on the results of the F test, it can be seen that f is with a significance level of 0.000 <0.05 then the degree of freedom (df) is (k-1) or the degree of the numerator and (n- k) for the degree of denominator where n = number of observations and k = the number of variables, then the F table is obtained of 3.08. So that the value of f is greater than f (33,426> 3.08). Thus the test results show that H0 is rejected and Ha is accepted. This indicates that together (simultaneously) the independent variables (training and motivation) have a significant effect on the dependent variable (performance).